Limites ao uso de inteligência artificial na Advocacia Pública Estadual - Souza, Márcio Cândido Costa de (2021)
Introduction: The State model outlined by the Federal Constitution of 1988 (CF/1988) contains several mechanisms of control and transparency of the State Public Administration. Among these mechanisms, it establishes the judicial representation of the States and the Federal District as an exclusive activity of state attorney (art. 132), which must always be guided by the constitutional principles of legality, impersonality, morality, publicity and efficiency (art. 37, caput). Mainly in a context of budgetary limitations for hiring personnel and the increasing judicialization of individual demands for public services, public managers started to see the use of artificial intelligence as a solution to the growing imbalance between the stagnant number of public lawyers and the growing volume of lawsuits. The problem is that the unlimited use of artificial intelligence may violate fundamental rights, control mechanisms and transparency inherent to the Managerial State model currently in force in Brazil, affronting CF/1988. The main objective of the research was to examine some constitutional limits for the use of artificial intelligence in the activities developed by state’s attorneys. As specific objectives, the research intended to present the factual and legal circumstances in wich the judicial representation of the States and the Federal District is exercised, to investigate the context of application of artificial intelligence to understand the benefits and risks related to the use of this technology in the legal field, as well as analyzing constitutional norms that limit the use of artificial intelligence in Public Advocacy through the systematic interpretation of CF/1988 (BRASIL, 1988) in light of general theory of fundamental rights in the perspective of Sarlet (2021). As for the methods and procedures, the research used the dialectical method and the qualitative approach, constituting a descriptive carried out through bibliographic and documentary research using secondary data, obtained mainly by surveying texts related to the interpretation of constitutional and legal norms pertinent to the problem under study. The result obtained was to find some constitutional limits that must be respected by the public manager when implementing or using artificial intelligence in the activity developed by state’s attorney office. Based on this result, the research presented, as a technical product obtained, a proposal for Resolution of the Procuradoria-Geral do Estado (State Attorney General's Council) establishing norms that define limits to the use of artificial intelligence in the state’s attorney office.